AROMATHERAPY AS A COMPLEMENT OF COVID-19 THERAPY - Dessy Abdullah Abdullah; Nadia Purnama Dewi; Ade Teti Vani; Rinita Amelia (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Aromatherapy helps COVID-19 patients to prevent, increase immunity, and relieve symptoms of COVID-19 so that it can be used as adjuvant COVID-19 therapy. This Community Service aims to introduce aromatherapy that can be used as a complementary therapy for COVID-19 and refute the myth that aromatherapy functions as the primary therapy for COVID-19. This activity is carried out in three stages, in the form of pre-test, presentation of material, and post-test. The pre-test was given together before the presentation of the material. The first material introduces aromatherapy, its benefits, and refuting the myth in the community, namely aromatherapy as the primary therapy for COVID-19. The last stage is to give a post-test after the delivery of the material. The participants of this service were 52 people, which was carried out online through the zoom application. This activity showed an increase in participants' knowledge about using aromatherapy as a complement of COVID-19 therapy.